Stress urinary incontinence after hysterectomy: a 10-year national follow-up study - Tulokas Sari; Mentula Maarit; Härkki Päivi; Brummer Tea; Jalkanen Jutta; Kuittinen Tanja; Mäkinen Juha; Sjöberg Jari; Tomas Eija; Rahkola-Soisalo Päivi (SPRINGER HEIDELBERG, 2025)
Purpose: Hysterectomy has been associated with increased risk for developing stress urinary incontinence (SUI) and having a SUI operation. We examined the long-term rate of SUI operations after hysterectomy and associated risk factors.
Methods: We followed up 5000 women without prior urinary incontinence (UI) who had a hysterectomy in a prospective FINHYST 2006 cohort study until the end of 2016 through a national health register. The main outcome was SUI operations, and secondary outcomes were outpatient visits for UI, and their association of preoperative patient and operation factors.
Results: During the median follow-up time of 10.6 years (IQR 10.3-10.8), 111 (2.2%) women had a SUI operation and 241 (4.8%) had an outpatient visit for UI. The SUI operation rate was higher after vaginal hysterectomy and laparoscopic hysterectomy (n = 71 and 28, 3.3% and 1.8%, respectively) compared to abdominal hysterectomy (n = 11, 0.8%). In a multivariate risk analysis by Cox regression, the association with vaginal hysterectomy and SUI operation remained significant when adjusted for vaginal deliveries, preceding pelvic organ prolapse (POP), uterus size, age and BMI (HR 2.4, 95% CI 1.1-5.3). Preceding POP, three or more deliveries and laparoscopic hysterectomy were significantly associated with UI visits but not with SUI operations.
Conclusion: After hysterectomy, 2.2% of women underwent operative treatment for SUI. The number of SUI operations was more than double after vaginal hysterectomy compared to abdominal hysterectomy, but preceding POP explained this added risk partially. Preceding POP and three or more vaginal deliveries were independently associated with UI visits after hysterectomy.